The Baltics and Bulgaria : Labor Markets in Hard-Peg Accession Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The paper examines labor market developments in the four hard-peg European Union (EU) accession candidates during transition, with a view toward understanding the persistent high unemployment experienced in each country. Despite the significant levels of unemployment in all four countries, labor market developments suggest that the strongest and earliest reformers have had the best labor market performance as well. It is crucial that all four countries continue their policies aimed at encouraging investment and job creation. Accession to the EU will present challenges to labor markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Bulgaria